Potential treatment of glutathione in bullfrogs with abnormal hepatic lipid metabolism revealed by hepatic lipid metabolism and serum metabolomics analysis - Su, Zehui; Gao, Fu; Shu, Rui; Cai, Kai; Fang, Shugaung; Lei, Xiaoting; Li, Dan; Hu, Kun (Frontiers in Cellular and Infection Microbiology, 2024)
With the continuous growth of bullfrog supply, it has become an important aquaculture species. Due to the lack of actionable industry standards and regulation, the misuse of anti-disease drugs and abnormal liver lipid metabolism in bullfrogs have become a major obstacle to the development of bullfrog aquaculture industry. Glutathione is a natural tripeptide that can be synthesized intracellularly, and its physiological functions mainly include the treatment of liver diseases, antioxidant, detoxification, anti-tumor, enhancement of immunity, and delaying aging. In this study, the therapeutic effect of glutathione on bullfrogs with abnormal liver lipid metabolism was revealed from hepatic lipid metabolism and serum metabolomics analysis. The survival rate, liver histomorphology, serum antioxidant enzyme activity, liver lipase activity and serum metabolomics, liver metabolomics were studied and analyzed by feeding the bullfrogs with abnormal lipid metabolism with glutathione for 20 days in the NC, FI and GSH groups.The results of the study showed that glutathione was able to repair the liver and improve the survival rate of bullfrogs with abnormal lipid metabolism; the activity of serum SOD enzymes was significantly increased; the activities of ACP and AKP were significantly decreased; the activities of HDL-C and T-CHO were significantly increased; and the activities of LDL-C, TBA, and TG were significantly decreased in the liver; the contents of metabolites, such as PC, PS, and PE were significantly up-regulated, and the levels of up-regulated Autophagy -other, Necroptosis and ErbB signaling pathway, and down-regulated Sphingolipid metabolism, D-Amino acid metabolism metabolic pathway, to some extent The metabolic pathways of Sphingolipid metabolism and D-Amino acid metabolism were down-regulated to alleviate the disorders of glycerophospholipid and amino acid metabolism to a certain extent, thus alleviating the abnormalities of liver lipid metabolism. The results showed that glutathione could effectively treat the liver lipid metabolism disorder of bullfrogs, promote the growth and development of bullfrogs, repair the liver function, reduce the inflammation, and promote the healthy and green development of bullfrog industry.